GIS-Based Risk Assessment and Regionalization of Drought Hazards in China - 张峰 黄敬峰 张丽文 王秀珍 (东华大学学报（英文版）, 2012)
Based on the monthly precipitation （1960 -2009 ） of China and associated regional socio-economie data, the spatial and temporal pattern of drought in China was assessed by applying a conceptual framework of disaster system theory, which used the hazard and vulnerability as two variables to define the risk of drought. Sichuan province suffered from the severe risk of drought, while Guangxi, Yunnan, Guizhou provinces, and Chongqing city could be classified as the moderate drought risk area of China. Additionally, Tibet plateau in the Northwest of China had the lowest risk of drought. The integrated data from this result provided the valuable information to cope with the drought in respect of optimization utilization of ]!and resources at the regional scale.